Toroidal mode number transition of the edge localized modes in the KSTAR plasmas. (16th October 2015) - Lee, J.E.; Yun, G.S.; Kim, M.; Lee, J.; Lee, W.; Park, H.K.; Domier, C.W.; Luhmann, N.C.; Ko, W.H.
Abstract: Rapid transitions of the toroidal mode number ( ) have been often detected during the evolution of the edge localized modes (ELMs) in the inter-ELM-crash periods of the KSTAR tokamak plasmas. The mode number transitions accompany changes of the mode frequency ( ) (e.g. changed from 8 to 5 while changed from 32 to 9 kHz). The observed transition phenomena have been diverse including small and large increase (or decrease) in the mode number and multiple transitions during a single inter-ELM-crash period. Two classes of the mode transitions were identified: non-overlapping transition and overlapping transition. The former case is characterized by the absence of coherent filamentary structure during the transition and the latter case is characterized by co-existence of two coherent filamentary structures with different mode numbers. Each transition process typically lasts a few hundreds to thousands of μ s.